(untitled) (London, 1997)
The great processes reshaping our world today can be summed up by the term "globalisation". Together with the communications revolution and massive urbanisation, it is reshaping theorganisation of global space. It is illustrated by technological change, pronounced economic growth, the dominance of giant corporations, ever more open markets and universal consumption. Dramatic developments have occurred in Asia-Pacific trade, investment, labour movements and political cooperation, marked for example by APEC, a giant free-trade area designed to encompass about 60% of the world's population and half the world's economy.
Keywords: Châu Á Thái Bình Dương,Pacific Area; Hội nhập kinh tế,Economic integration